2016
DOI: 10.1063/1.4966986
|View full text |Cite
|
Sign up to set email alerts
|

A modular microfluidic bioreactor with improved throughput for evaluation of polarized renal epithelial cells

Abstract: Most current microfluidic cell culture systems are integrated single use devices. This can limit throughput and experimental design options, particularly for epithelial cells, which require significant time in culture to obtain a fully differentiated phenotype. In addition, epithelial cells require a porous growth substrate in order to fully polarize their distinct apical and basolateral membranes. We have developed a modular microfluidic system using commercially available porous culture inserts to evaluate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Here, the leak through the MDCK cells was minimal at less than 1 mg/cm 2 per day and significantly lower than that through human cells. We have previously shown that human kidney cell monolayers have a 10-20 mg/cm 2 per day inulin leak (Brakeman et al, 2016), supporting the conclusion that the hOCT2/hMATE1 MDCK cells formed a robust monolayer.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Here, the leak through the MDCK cells was minimal at less than 1 mg/cm 2 per day and significantly lower than that through human cells. We have previously shown that human kidney cell monolayers have a 10-20 mg/cm 2 per day inulin leak (Brakeman et al, 2016), supporting the conclusion that the hOCT2/hMATE1 MDCK cells formed a robust monolayer.…”
Section: Discussionsupporting
confidence: 72%
“…Device Fabrication and Assembly. We have previously published our design for a parallel plate bioreactor that provides a fluid flow path of adjustable height across the apical side of the cells and a static reservoir on the basal side (Brakeman et al, 2016). For the work presented here, we adapted our previous design to create a multiplexed device with four separate flow paths to allow for testing four biologic conditions at once ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Discrete sensing channels enabled the flexibility to replenish and replace the beads as desired prior to saturation. In addition, the group was able to demonstrate a multiplexing capability with both TGF-β1 and hepatocyte growth factor simultaneously using multiple sets of beads with different fluorescent markers.
Figure 9Examples of Instrumented Organ-on-chip Models of the Liver and Kidneys(A) Detection of TGF-β1 within a reconfigurable device to allow communication between injured hepatocytes and stellate cells via an aptamer-based electrochemical sensor.(B) On-chip detection of the hepatocyte growth factor and TGF-β1 secreted by primary hepatocytes via a fluorescent-bead-based optical sensor.(C) Transferrin and albumin production from human primary hepatocytes cultured in the bioreactor quantified via a bead-based electrochemical immunosensor.(D) Continuous real-time monitoring of hepatocyte metabolic function via a glucose/lactate enzyme-based electrochemical sensors and oxygen sensing phosphorescent microprobes.(E) Hepatocyte oxygen consumption rate assessed via inkjet-printed electrochemical dissolved oxygen sensors and commercial Clark-type sensors.(F) Permeability study of an MDCK-2 cell monolayer cultured on the membrane of a bilayer chip via TEER electrodes.(G) Assessment of renal epithelial cell growth and tight junction integrity quantified within a continuous fluid shear stress model via integrated TEER electrodes.(H) TEER measurements from a human renal epithelial cell monolayer cultured in a multi-use microfluidic device with integrated electrodes.(I) Electrical cell–substrate impedance monitoring of MDCK-2 cells to investigate wound healing and barrier integrity via an organic electrochemical transistor.(J) Electrochemical measurement of dissolved oxygen, Na + and K + ion concentration, and pH in kidney exactments via potentiometric and amperometric electrodes.Reprinted and adapted with permission from: A (Zhou et al., 2015); B (Son et al., 2017); C (Riahi et al., 2016); D (Bavli et al., 2016); E (Moya et al., 2018b); F (Douville et al., 2010); G (Ferrell et al., 2010); H (Brakeman et al., 2016); I (Curto et al., 2017); and J (Moya et al., 2018a). TGF-β1, transforming growth factor; MDCK-2, Madin Darby canine kidney-2; TEER, transepithelial electrical resistance.
…”
Section: Liver-on-chipmentioning
confidence: 99%
“…Reprinted and adapted with permission from: A (Zhou et al., 2015); B (Son et al., 2017); C (Riahi et al., 2016); D (Bavli et al., 2016); E (Moya et al., 2018b); F (Douville et al., 2010); G (Ferrell et al., 2010); H (Brakeman et al., 2016); I (Curto et al., 2017); and J (Moya et al., 2018a). TGF-β1, transforming growth factor; MDCK-2, Madin Darby canine kidney-2; TEER, transepithelial electrical resistance.…”
Section: Liver-on-chipmentioning
confidence: 99%
“…This parameter serves to identify the formation of complex surface morphologies such as microvilli structures (Wang et al, ; Wegener, Abrams, Willenbrink, Galla, & Janshoff, ). Some authors have developed microfluidic systems with integrated electrodes (Brakeman et al, ; Ferrell et al, ) or also organic electrochemical transistors (Curto et al, ) for the evaluation of renal epithelial cells under flow.…”
Section: Introductionmentioning
confidence: 99%